α-Amylase enzyme inhibition relevant to type II diabetes by using functional yogurt with Cinnamomum verum and Stevia rebaudiana - Aneela Hameed; Fartashia Ashraf; Muhammad Junaid Anwar; Adnan Amjad; Muzzamal Hussain; Muhammad Imran; Ahmed Mujtaba; Ishtiaque Ahmad; Muhammad Shoaib Aslam; Ahmed H. El-Ghorab; Mohammed M. Ghoneim; Mohamed E. Shaker; et al. (Food and Agricultural Immunology)
Type II diabetes prevalence rate is increasing globally. That’s why recently, our research group has worked on functional yogurts made from milk of different species by using functional ingredients to explore their α-amylase inhibitory activity relevant to management of type II diabetes. Sixteen yogurt treatments were made from milk of four species, cow, goat, buffalo, and camel by incorporating Stevia rebudiana (5 ml) and Cinnamomum verum (10 ml) extract. The physicochemical attributes and α-amylase inhibition rate of prepared functional yogurts were evaluated on 1st, 7th, 14th and 21st days of storage. Significant changes in physicochemical properties were observed in cinnamon and stevia camel milk yogurt. All yogurts showed increase in inhibition rate till 14th day and decline on 21st day of storage period. However, cinnamon camel milk yogurt showed 63% α-amylase inhibition on 1st day,cinnamon and stevia camel milk yogurt showed highest α-amylase inhibition (61.15%) on 14th day.